Simulating climate and energy policy with agent-based modelling: The Energy Modelling Laboratory (EMLab). (October 2017) - Chappin, Emile J.L.; de Vries, Laurens J.; Richstein, Joern C.; Bhagwat, Pradyumna; Iychettira, Kaveri; Khan, Salman
Abstract: We present an approach to simulate climate and energy policy for the EU, using a flexible and modular agent-based modelling approach and a toolbox, called the Energy Modelling Laboratory (EMLab). The paper shortly reviews core challenges and approaches for modelling climate and energy policy in light of the energy transition. Afterwards, we present an agent-based model of investment in power generation that has addressed a variety of European energy policy questions. We describe the development of a flexible model core as well as modules on carbon and renewables policies, capacity mechanisms, investment behaviour and representation of intermittent renewables. We present an overview of modelling results, ongoing projects, a case study on current reforms of the EU ETS, and we show their relevance in the EU context. Highlights: We present an approach to simulate climate and energy policy for the EU. We reviews core challenges and approaches for modelling climate and energy. We developed a flexible and modular agent-based modelling approach and a toolbox. We present an configurable agent-based model of investment in power generation. We describe a flexible model core and separate policy modules.